EVALUASI SISTEM PROTEKSI KEBAKARAN PADA PROYEK PEMBANGUNAN GEDUNG RUMAH SAKIT X DI KOTA GRESIK - MAULANA, YUSKI ALMAYDA (Universitas Negeri Surabaya, 2023)
The construction project of hospital x in Gresik City requires a reliable fire protection system so that the building can take proactive action against fire risks at an early stage. But in the phenomenon, building fires in Indonesia show that some managers or building owners entrust the initial fire anticipation actions to the Fire Department. Objective To find out how far the application of fire hazard protection listed in Permen PU no.26/PRT/M/2008 and the Reliability Value of the Building Safety System in the x hospital building construction project. This research uses descriptive-quantitative method. Information obtained from systematic observations, library studies and interviews with various parties / experts on fire safety systems. The results of data collection and discussion are analysed or the problems found are answered, after which conclusions and suggestions are given regarding the building fire reliability system. Based on the application of these regulations regarding the fire system which is assessed using a Likert scale on the building at Hospital X, the results of the application of an average of 4.57 Likert scale values with a percentage of 91.4% of the measurement criteria are obtained. This shows that the building has a fire control system that is in accordance with the application. The results of the calculation of the Building Safety Reliability Value indicate 91.6% and is classified in the